Financial Cost and Benefit Analysis of Flower Induction Chemical Off-Season Longan Using in Tambon Baanpae Amphoe Jomthong Chiang Mai Province - กิจเศรณี ธนิดา (Business Administration and Management Journal Review, 2013)
The purposes of this research were to study the costs and the financial benefits from the use of a chemical driving Longan trees to blossom off the season and to study the problems of the production of off-season Longans as well as to suggest some solutions of the obstacles of the production of off – season Longans . The result show that the production of Longans in the group with the use of Potassium gave out NPV as 101,691.49 bath and BCR as 1.69 and IRR as 20.48 % , whereas the other group with San Somboon 99 gave out NPV as 200,506.15 bath., and BCR as 2.45 and IRR as 33.08 % . From the studies on the fluctuation of the investment of the production of off-season Longans it appeared to be profitable or worth the investment. This meant it was at low risk for the investment of the off-season Longans.